Evaluation of inhibin-B hormone, FSH, and Testosterone in serum of infertile men - Al-Khateeb, Shatha; Hussein, Sabah M.; Ibrahem Dahy, Ahmad A. A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Serum levels of inhibinB hormone , FH and testosterone hormone in serum of infertile men and compare the results with the fertile men (cotrols). Thirty patients (infertile men) healthy 14 controls included in this study.mean serum inhibinB ,testosterone and FH level of oligospermia and azoospermia groups were significantly differences than these both control group. Objective: The study was planned to evaluate serum levels of inhibinB hormone , FSH and testosterone hormone in infertile men and compare the results with these fertile men (Controls). Materials & Methods: Thirty patients (infertile men) and 14 healthy controls (fertile men) included in this study, Age range (24 to 45 years). The patients (30) were divided into two groups, oligoospermia and azoospermia. Results: Mean serum inhibinB , testosterone and FSH levels of oligospermia and azoospermia groups were significantly differences than these both control group, while the difference between mean of serum inhibin B ,testosterone and FSH of oligospermia and oligospermia group , was not significant except the FSH (P.value=0.039). Conclusion: The decrease in serum inhibinB and testosterone levels not the increase in the level of FSH hormone in infertile men provide evidence that levels can be used as reliable markers in the diagnostic criteria of male infertility .